PENGGUNAAN ALAT PERAGA PAPAN ALJABAR DALAM PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT UNTUK SISWA PKBM BUDI LUHUR - Triyani Triyani; Niken Larasati; Ari Wardayani; Agustini Tripena; Slamet Riyadi (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2022)
This Community Service activity aims to improve the quality and motivation of mathematics learning, especially the addition and subtraction of integers for PKBM Budi Luhur Pekaja Banyumas students. This learning activity is carried out offline at the beginning of the odd semester of the 2022/2023 academic year by involving 7 (seven) graders. The learning method used is lectures and demonstrations of the use of teaching aids called 'algebra boards'. Algebra board teaching aids are concrete teaching aids resulting from the development of semi-concrete teaching aids, namely the number line that is used to explain the addition and subtraction of integers. The evaluation of the success of the learning activity results is based on the pre-test and post-test scores given to students before and after using the algebra board props. The results of the evaluation showed that the average score of students increased by 64.7% for the material of adding integers and 39.1% for the material of subtracting integers.